An Analysis of NPA in Indian Commercial Banks (What ails Non Performing Assets) - Krishna, A. R (Journal of Commerce and Trade, 2008)
NPA is non-performing assets, which are not producing any new income. Indian banking industry has undergone several changes during the liberalization process. However, one nagging problem affecting the baking sector has been the high level of non- performing assets. High non-performing assets affect the profitability, productivity, capital adequacy and competitiveness of banks. Management of NPAs , therefore, assumes significance in management of banks. Regulators and policy makers for banks have been taking measures to bring down the level of NPA in Indian commercial banks. This paper analyses the trend of NPAs in the last five years and suggest measures to reduce them. The reforms measures and policy initiatives have resulted in reducing the level of NPAs in Indian commercial banks. Categorywise analysis shows that the public sector banks have hier levls of NPAs in comparison to private and foreign banks. Sectorwise analysis reveals that priority sector lending accountsf or major portion of NPAs in public sector banks, while non-priority sector lending account for major portion NPAs in private and foreign banks. Agriculture sector also is an important contributor to the NPAs in commercial banks.The paper is divided into three sections. Section I describes the concept, causes and consequences of NPA. Section II Analyses the trend of non-performing assets in Indian commercial banks. Section III contains conclusive remarks.